Men as offenders while women as victims: a corpus-based study of men and women in the United Nations - Xue, Jiaqi (Frontiers in Communication, 2025)
This study examines the representations of men and women in the United Nations Parallel Corpus-English (UNPC-E) by using the corpus linguistics tool, Sketch Engine. Three types of grammatical collocations were explored, including verbs frequently collocating with MAN and WOMAN when they serve as subjects and objects, and adjectives used as predicates in relation to them. The results reveal that within the UN discourse, men are often portrayed as offenders while women tend to be depicted as victims. This pattern of representations may stem from the UN’s agenda focused on addressing gender-based inequality, as well as from the conventional reporting bias that might have influenced data availability. In general, this study broadens the scope of research in the field of gender and corpus linguistics to some extent, offering a more comprehensive and international perspective on the representations of men and women through the analysis of the UN corpus.